Is there a role for a learner education handover as part of the Medical Council of Canada assessment and licensing process? - Nickell, Leslie; Kassam, Aliya; Bandiera, Glen (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
The transition from undergraduate medical education (UGME) to postgraduate medical education (PGME) is a time of vulnerability for medical schools, postgraduate residency programs, and most importantly, traineesThere is a disconnect between the UGME and PGME experience. Student information shared by UGME is primarily summative of knowledge and skills; PGME programs are unaware of specific learner accommodation requirements, tailored supervisory needs, or potential professionalism concerns identified during UGMEThis lack of integration between UGME and PGME increases potential risk to learners, postgrad programs and patientsBetter linkages and communication along the education continuum could optimize learning and reduce inefficiency and riskThe Medical Council of Canada (MCC) has asked if there is a role for a learner handover (LH) within their licensing processes; however the intended purpose of an LH must first be determinedA Canadian-based LH referred to as a Learner Education Handover (LEH) model including disclosure of student learning/disability accommodation needs, general health concerns, EDI/religious requirements, professionalism concerns, recommendations for special focus in residency of specific areas of medical knowledge/skill is described.Findings from beta and pilot testing support the value and feasibility of the LEH model. Fundamental principles are outlined:LEH occurs post-residency matchLEH should be forward facing; focused on ongoing or recurring learner issues and needsLearners must be included in the processImplementation would require participation by all Canadian medical schools and all learnersImplementation challenges include:Ensuring learner safety following information disclosureEngaging UGME DeansProtection of information ensuring a ‘need-to-know’ status is maintainedIncorporating the LEH into the licensing activity could enable the MCC to support a system that proactively responds to learner needs, optimizes physician performance and promotes safe, high quality patient care.